2004
DOI: 10.1590/s0004-282x2004000500022
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoglifia e composição corporal em apnéia obstrutiva do sono

Abstract: A síndrome da apnéia obstrutiva do sono (SAOS) tem como principal fator de risco a obesidade e acredita-se que fatores genéticos poderiam contribuir na sua patogênese. O objetivo deste estudo foi descrever as características antropométricas e dermatoglíficas dos portadores de SAOS. Foram mensurados: indice de massa corporal (IMC); indice de conicidade, gordura corporal relativa, somatotipo e coletadas as impressões digitais. Trinta e um casos de SAOS foram comparados a número igual de controles. Pelo IMC e gor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…In our study, a comparison between men and women regarding the body composition in relationship with the severity of OSAHS was not possible, because of the small number of female patients ([9] females vs. 21 males).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a comparison between men and women regarding the body composition in relationship with the severity of OSAHS was not possible, because of the small number of female patients ([9] females vs. 21 males).…”
Section: Discussionmentioning
confidence: 99%
“…A weight increase or obesity can cause patients with mild OSAS to exhibit moderate to severe OSAS ( 18 ). Although there have been many studies examining the associations between OSAS and obesity ( 19 , 20 ), a limited number of studies have examined the associations between OSAS and the patient’s somatotype. Mecanti et al assessed individual somatotypes in order to evaluate the body compositions of patients with OSAS, and they reported that, in the mesomorphic dominant individuals, there were increases in the severe OSAS symptoms and OSAS dependent morbidity rate ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…22 Entretanto ao considerarmos a distribuição de padrões em cada dedo, verifica-se a peculiaridade dos DM nos diferentes grupos, conforme indicado na Tabela 2. Para as voluntá-rias com excesso de gordura corporal, a presença de arcos é superior na maioria dos quirodáctilos, com as presilhas em menor freqüência quando comparadas aos dois outros estudos.…”
Section: Tabelaunclassified